ShockOmics: multiscale approach to the identification of molecular biomarkers in acute heart failure induced by shock. Issue 1 (December 2016) - Aletti, Federico; Conti, Costanza; Ferrario, Manuela; Ribas, Vicent; Bollen Pinto, Bernardo; Herpain, Antoine; Post, Emiel; Romay Medina, Eduardo; Barlassina, Cristina; de Oliveira, Eliandre; Pastorelli, Roberta; Tedeschi, Gabriella; et al.
Abstract Background TheShockOmics study (ClinicalTrials.gov identifier NCT02141607) is a multicenter prospective observational trial aimed at identifying new biomarkers of acute heart failure in circulatory shock, by means of a multiscale analysis of blood samples and hemodynamic data from subjects with circulatory shock. Methods and Design Ninety septic shock and cardiogenic shock patients will be recruited in three intensive care units (ICU) (Hôpital Erasme, Université Libre de Bruxelles, Belgium; Hospital Universitari Mutua Terrassa, Spain; Hôpitaux Universitaires de Genève, Switzerland). Hemodynamic signals will be recorded every day for up to seven days from shock diagnosis (time T0). Clinical data and blood samples will be collected for analysis at: i) T1 < 16 h from T0; ii) T2 = 48 h after T0; iii) T3 = day 7 or before discharge or before discontinuation of therapy in case of fatal outcome; iv) T4 = day 100. The inclusion criteria are: shock, Sequential Organ Failure Assessment (SOFA) score > 5 and lactate levels ≥ 2 mmol/L. The exclusion criteria are: expected death within 24 h since ICU admission; > 4 units of red blood cells or >1 fresh frozen plasma transfused; active hematological malignancy; metastatic cancer; chronic immunodepression; pre-existing end stage renal disease requiring renal replacement therapy; recent cardiac surgery; Child-Pugh C cirrhosis; terminal illness. Enrollment will be preceded by the signature of the Informed Consent by the patient or his/her relatives and by the physician in charge. Three non-shock control groups will be included in the study: a) healthy blood donors (n  = 5); b) septic patients (n  = 10); c) acute myocardial infarction or patients with prolonged acute arrhythmia (n  = 10). The hemodynamic data will be downloaded from the ICU monitors by means of dedicated software. The blood samples will be utilized for transcriptomics, proteomics and metabolomics ("-omics ") analyses. Discussion ShockOmics  will provide new insights into the pathophysiological mechanisms underlying shock as well as new biomarkers for the timely diagnosis of cardiac dysfunction in shock and quantitative indices for assisting the therapeutic management of shock patients.